THE EVALUATION OF TRIPLE, QUADRUPLE, AND LEVOFLOXACIN-BASED THERAPY IN THE MANAGEMENT OF HELICOBACTER PYLORI INFECTION AMONG DYSPEPTIC PATIENTS - Mohammed, Mohammed O.; Arif, Dunya M.; Mohammed, Mohsin A. (Journal of Sulaimani Medical College, 2019)
Background The eradication rate for the first line therapy in H. pylori infection declined worldwide as a result of resistance development; however other therapies as quadruple and levofloxacin-based therapy are also used and have different eradication rate. Objectives To assess the response rate of H. pylori infection for different drug’s regimens (triple, quadruple, and levobased), and evaluate the effect of age, gender, body mass index and compliance of the patients on the regimens response rate. Methods A cross- sectional study, conducted in Kurdistan Center for Gastroenterology and Hepatology (KCGH) in Sulaimani, from April 2018 –November 2018. The study Included 753 dyspeptic patients, H. pylori were positive in 430 (57.1%) patients. Demographic data, anthropometric measures, and clinical presentations were recorded for the participants. The participants were randomly treated with one of the standard H. pylori eradication regimens (triple, quadruple or levobased), they have been followed up for 45 days and rechecked for H. pylori. Results The mean age of the patients was 39.8± 15.6 years, and the mean Body Mass Index was 25.7± 6.1kg/m2, 182(42.3%) were male and 248 (57.7%) were female. The rates of responses were (84.4%, 89.4%, and 97.4%) for the triple, quadruple and levobased regimens respectively. The most adverse effects were dizziness and metallic taste recorded in 30.3% in the quadruple group. Statistically, a significant difference was found in the response rate among the triple, quadruple and levobased regimens (p= 0.033). There were no significant differences in the response rate among the three regimens group regarding age, gender, and body mass index. More than 95% in those who completed follow up were adherent to their regimens. Conclusion Triple and quadruple regimens are still effective for H. pylori eradication, but have more adverse effects than levobased regimens. Levobased regimen has highest eradication rate for H. pylori, better compliance, and least adverse effects.
Keywords: H. pylori; Triple therapy; Quadruple therapy; Levofloxacin based therapy